2020
DOI: 10.1038/s41419-020-03264-5
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of eIF2α signaling pathway attenuates obesity-induced non-alcoholic fatty liver disease in an ER stress and autophagy-dependent manner

Abstract: Non-alcoholic fatty liver disease (NAFLD) is the most common liver disorder and frequently exacerbates in postmenopausal women. In NAFLD, the endoplasmic reticulum (ER) plays an important role in lipid metabolism, in which salubrinal is a selective inhibitor of eIF2α de-phosphorylation in response to ER stress. To determine the potential mechanism of obesity-induced NAFLD, we employed salubrinal and evaluated the effect of ER stress and autophagy on lipid metabolism. Ninety-five female C57BL/6 mice were random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 50 publications
0
22
0
Order By: Relevance
“…SAL is under development for hepatic steatosis by altering cellular stress and autophagy through eIF2α signaling [ 46 ], treatment of osteogenesis imperfect [ 47 ], and SAL efficiently blocked osteoporosis in mice [ 48 ]. To move SAL to clinical trials an oral formulation is required; mice have been treated with SAL in soymilk, which restored primordial follicles production in galactosemia mice [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…SAL is under development for hepatic steatosis by altering cellular stress and autophagy through eIF2α signaling [ 46 ], treatment of osteogenesis imperfect [ 47 ], and SAL efficiently blocked osteoporosis in mice [ 48 ]. To move SAL to clinical trials an oral formulation is required; mice have been treated with SAL in soymilk, which restored primordial follicles production in galactosemia mice [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…SAL is under development for other diseases such as hepatic steatosis by altering cellular stress and autophagy through eIF2α signaling (44), treatment of osteogenesis imperfect (45), and SAL efficiently blocked osteoporosis in mice (46). To move SAL to clinical trials an oral formulation is required; mice have been treated with SAL in soymilk, which restored primordial follicles production in galactosemia mice (47) however, the design of novel and safer alternatives for HU is highly desirable for people with SCD.…”
Section: Discussionmentioning
confidence: 99%
“…ER stress has long been recognized as one of the autophagy inducers [36], which can regulate autophagy through different UPR signaling pathways (Figure 6) [22]. The previous research confirmed that autophagy plays a pivotal role in various forms of liver damage [37][38][39][40]. However, there is no study about autophagy in liver after IQ exposure.…”
Section: Discussionmentioning
confidence: 99%